Pengaruh Penyuluhan ASI Eksklusif Menggunakan Media Lembar Balik terhadap Pengetahuan dan Sikap Ibu Hamil di Wilayah Kerja Puskesmas Mowewe Kabupaten Kolaka Timur - Fatmawati, Fatmawati; Nurwanti, Nurwanti (Jurnal Gizi Ilmiah, 2017)
The coverage of exclusive breastfeeding has not yet reached the target, this is caused by several factors including the low knowledge of mothers about the benefits of exclusive breastfeeding for the growth and development of babies, so they do not give a good attitude towards the implementation of exclusive breastfeeding. This study aims to determine the effect of exclusive breastfeeding counseling on the knowledge and attitudes of pregnant women in the working area of ​​Mowewe Health Center, East Kolaka Regency. This type of research is a quasi-experimental where the design form used is a one group pre-test-post test design, which was carried out in April 2017 at the Mowewe Health Center Work Area, East Kolaka Regency. The research sample used total sampling from the existing population, which amounted to 30 people. Data were analyzed using statistical t-test at the 95% confidence level (α 0.05). There was an increase in the average knowledge of respondents after counseling with a value of 0.8666. Statistical test using The t-test at the 95% confidence level (α=0.05) showed a value of 0.000. There was an increase in the average attitude of respondents after counseling with a value of 1.1000. Statistical test using t-test at the 95% confidence level (α=0.05) showed a value of 0.000. There was an effect of exclusive breastfeeding counseling on knowledge of pregnant women (p value = 0.000). There is an effect of exclusive breastfeeding counseling on the attitude of pregnant women (p value = 0.000)